The Effect Of Operational Audit and Good Clinical Governance On The Effectiveness Of Health Services At Hikmah Hospital Makassar City - Siti Reziyah Kamelia Pertiwi; Abd. Rahman Mus; Andika Pramukti (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2024)
Hospitals have a very important role in the implementation of health services in the community, this study aims to examine the Effect of Operational Audit and Good Clinical Governance on the Effectiveness of Health Services at Hikmah Hospital Makassar City. The variables in this study are the influence of operational audits and good clinical governance as independent variables, and the effectiveness of health services in hospitals as dependent variables. This study used a quantitative approach, using primary data through the distribution of questionnaires. The respondents in this study were employees from Hikmah Hospital Makassar City which amounted to 118 people. Data collection used by researchers in conducting this study, namely with primary data sources. Data collection method in research using questionnaires. The analysis requirements are tested in the form of normality tests, multicollinearity tests, and heteroscedasticity tests. The data analysis technique used in this study is the regression analysis technique of two predictors or multiple analysis. Data analysis techniques are carried out with descriptive statistical analysis and using SPSS 27.00. The results showed that it shows that operational audit and internal control variables have a positive and significant effect on the effectiveness of health services. The results showed that operational audit variables and good clinical govenance simultaneously (together) had a positive and significant effect on the effectiveness of health services.